Applying Exploratory Structural Equation Modeling to Examine the Student-Teacher Relationship Scale in a Representative Greek Sample - Tsigilis, Nikolaos; Gregoriadis, Athanasios; Grammatikopoulos, Vasilis; Zachopoulou, Evridiki (Frontiers in Psychology, 2018)
Teacher-child relationships in early childhood are a fundamental prerequisite for children’s social, emotional, and academic development. The Student-Teacher Relationship Scale (STRS) is one of the most widely accepted and used instruments that evaluate the quality of teacher-child relationships. STRS is a 28-item questionnaire that assess three relational dimensions, Closeness, Conflict and Dependency. The relevant literature has shown a pattern regarding the difficulty to support the STRS factor structure with CFA, while it is well documented with EFA. Recently, a new statistical technique was proposed to combine the best of the CFA and EFA namely, the Exploratory Structural Equation Modeling. The purpose of this study was (a) to examine the factor structure of the STRS in a Greek national sample. Towards this end, the Exploratory Structural Equation Modeling framework was applied in order to overcome the limitations of EFA and CFA, (b)to confirm previous findings about the cultural influence in teacher-child relationship patterns, and(c) to examine the invariance of STRS across gender and age. Early educators from a representative Greek sample size of 535 child care and kindergarten centers completed the STRS for 4158 children. CFA as well as ESEM procedures were implemented. Results showed that ESEM provided better fit to the data than CFA in both groups, supporting the argument that CFA is an overly restrictive approach in comparison to ESEM for the study of STRS. All primary loadings were statistically significant and were associated with their respective latent factors. Contrary to the existing literature conducted in USA and northern Europe, the association between Closeness and Dependency yielded a positive correlation. This finding is in line with previous studies conducted in Greece and confirm the existence of cultural differences in teacher-child relationships. In addition, findings supported the configural, metric, scalar and variance/covariance equivalence of the STRS between males and females and between preschoolers (3-5years) and early primary years (5-7 years). Latent factor means comparisons showed that females seem to have a warmer and more dependent relationship with their teachers and are less conflictual in comparison to males.